The Plight of Feeling : Sympathy and Dissent in the Early American Novel. - Stern, Julia A. (University of Chicago Press, 1997)
American novels written in the wake of the Revolution overflow with self-conscious theatricality and impassioned excess. In The Plight of Feeling, Julia A. Stern shows that these sentimental, melodramatic, and gothic works can be read as an emotional history of the early republic, reflecting the hate, anger, fear, and grief that tormented the Federalist era. Stern argues that these novels gave voice to a collective mourning over the violence of the Revolution and the foreclosure of liberty for the nation's noncitizenswomen, the poor, Native and African Americans. Properly placed in the contex.